(untitled) (Linguostylistic Studies, 2020)
The article deals with the analysis of the grammatical features of Lesya Ukrainka’s individual style. In the focus is the identification of the locative functions in the fairy-drama “The Forest Song”. Locative is defined as a component of the semantic-syntactic structure of a sentence, dependent on a verbal predicate that expresses varieties of spatial meaning. The article argues the notion of syntactic dependency applicability in the analysis of a sentence structure. The study has revealed that the predicates expressing the locative dependency have the correlated semantics in sentence constructions. In the semantic-syntactic structure of sentence constructions, predicates of static semantics, predicates of process, and predicates of action determine the locative’s components. The author lays emphasis on the semantic meanings of the locative’s components. They are dependent on the predicates of static semantics, predicates of process, and predicates of action. In the sentence structures of the fairy-drama The Forest Song, most locatives’ components express static location, the starting point of movement, a path of movement, and the destination point. The semantic special features of syntactic units represent Lesya Ukrainka’s holistic worldview, indicate her individual style. The locative reflects the world around represented in spatial nominations. The explicit locative component has been recorded in the sentence constructions with predicates of static semantics as well as there are elliptical sentences with the implicit predicate of static semantics. The predicates of process and action predetermine explicit and implicit locative components. It was found that the locative is mainly represented by prepositional case forms. It turns out that the distinctive feature of all sentences with locative components is presence of prepositions as markers of locative dependency. The locative components are presented in two-member and one-member sentences, in elliptical and imperative sentence constructions.